Strengthening the emergency health response to children wounded by explosive weapons in conflict - Mehmet Emin Çelikkaya; Emily Mayhew; Emmanuel A Ameh; Paul Reavley; Hannah Wild; Barclay Stewart (BMJ Publishing Group, 2022)
The 2022 war in Ukraine has highlighted the unacceptable consequences wrought on civilians and health infrastructure by conflict. Children are among the most vulnerable of those affected and constitute an increasing percentage of non-combatants injured in conflicts globally. A disproportionate number of these injuries are caused by blast mechanisms from munitions including 'conventional' landmines and indiscriminate explosive weapons such as barrel bombs and improvised explosive devices. In 21st century conflict, children are no longer only accidental casualties of war, but are increasingly targeted by parties through acts such as bombing of school buses and playgrounds, conscription as child soldiers, and use as human shields. In the present viewpoint article, we review the state of pediatric blast injury studies, synthesizing current understandings of injury epidemiology and identifying gaps in research to advance the field towards a concrete agenda to improve care for this vulnerable population.